A comparative study of the efficacy of intra-articular injection of different drugs in the treatment of mild to moderate knee osteoarthritis: A network meta-analysis. Issue 12 (24th March 2023) - Xue, Yuan; Wang, Xuan; Wang, Xiuming; Huang, Li; Yao, Aina; Xue, Yan
Abstract : Background: Knee osteoarthritis (KOA) has a high clinical prevalence and frequently interferes with patients normal lives. In KOA patients, evidence suggests that intra-articular (IA) injection improves joint function and decreases discomfort. Several IA injection treatments are used in daily practice to improve symptomatic control of knee osteoarthritis, but their efficacy is frequently disputed. Methods: This network meta-analysis compares the efficacy of different IA injections for mild to moderate knee osteoarthritis. Seven databases (PubMed, EMBASE, Web of Science, Cochrane Library, China Biology Medicine disc, WanFang, and China National Knowledge Infrastructure) were searched for randomized controlled trials published up to and including December 20, 2021, and final follow up indicators were used. Visual analogue scale (VAS) score and The Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index (WOMAC) score change from baseline were the primary outcomes. We used the Cochrane risk of bias tool to assess the quality and risks of biases of papers. We calculated the weighted mean difference (WMD) and 95% confidence interval (CI) for each outcome. State (Version 15.1, Texas, USA) and SPSS (Version 20, Chicago, USA) was used in all statistical analyses, and Review Manager (version 5.4) was used in assessing the risks of biases. Results: Our study included 16 randomized controlled trials with a total of 1652 patients. platelet-rich plasma (PRP) IA injection therapy had the highest likelihood of being the best intervention in reducing WOMAC pain (surface under the cumulative ranking area [SUCRA] 84.7%), stiffness (SUCRA 95.1%), and function (SUCRA 98.5%) scores, according to the SUCRA. The best measures for lowering the WOMAC total and VAS scores were IA injection platelet-rich plasma-derived growth factor (SUCRA 84.9%) and hyaluronic acid and platelet-rich plasma (SUCRA 84.9%). In the VAS score group, PRP outperformed hyaluronic acid (HA) (WMD 1.3, 95% CI 0.55–2.55) and corticosteroids (CS) (WMD 4.85, 95% CI 4.02–5.08), according to the forest map results. PRP also outperformed CS (WMD 14.76, 95% CI 12.11–17.41), ozone (WMD 9.16, 95% CI 6.89–11.43), and PRP + HA (WMD 2.18, 95% CI 0.55–3.81) in the WOMAC total score group. Furthermore, PRP outperforms other drugs in terms of reducing WOMAC function, stiffness, and function score. Conclusion: In patients with mild to moderate KOA, IA injection PRP outperformed IA injection ozone, HA, CS, platelet-rich plasma-derived growth factor, and hyaluronic acid and platelet-rich plasma in terms of pain, stiffness, and dysfunction.